A). 4x - (x + 6) + 4 dla x = jedna - trzecia
b). (x <do potęgi drugiej > +1) - ( x <do potęgi drugiej> - 2) + 10 dla x = 2 ,2
.C = ( a + 4b) - (5 + 2a) - (3b - 5) A = - 0,1 B = 0,2
D = ( -a do potęgi drugiej + 2ab - 1) + (a do potęgi drugiej - 4ab + 5) A = 1/4 B = 2

3

Odpowiedzi

  • hevi
  • Początkujący
2010-02-19T20:21:19+01:00
A) 5
b) 1/3
c) -1,1
d) 0
1 1 1
2010-02-19T20:28:43+01:00
A) 4x- (x+6) + 4 = 4x - x -6 + 4 = 3x - 2 = 3* 1/3 -2 = 1-2= -1
b) (x2 = 1) - (x2 - 2) + 10= x2+1 - x2+ 2+10 i coś tu jest źle bo mi nie wychodzi
c) (a + 4b) - (5 + 2a) - (3b - 5) = a = 4b -5 - 2a - 3b + 5= -a +b = 0,1 +0,2= 0,3
d) (a2 + 2ab - 1) + (a2 - 4ab+ 5) = -a2+ 2ab- 1 + a2 - 4ab + 5 = 2ab = 2 * 2/4 *2 = 1



* razy
x2 x do kwadratu
2010-02-19T20:33:07+01:00
A) 4x-x-6+4=-2+3x
3x=1/3*3=1
2+1=3

b)(x <do potęgi drugiej > +1) - ( x <do potęgi drugiej> - 2) + 10=x^2+1-x^2-2+10=9

c)( a + 4b) - (5 + 2a) - (3b - 5) =a+4b-5-2a-3b+5=-a+b=-0,1+0,2=0,1

d)( -a do potęgi drugiej + 2ab - 1) + (a do potęgi drugiej - 4ab + 5)=2ab-1-4ab+5=-1+4.5-9+5=0,5